2021
DOI: 10.31018/jans.v13i2.2674
|View full text |Cite
|
Sign up to set email alerts
|

Morpho-anatomical characterization of Rhizopogon himalayensis - Cedrus deodara mycorrhiza

Abstract: Rhizopogon himalayensis (Castellano, S.L. Miller, Singh & Lakhanpal) A.B. Mujic & M.E. Sm., comb. nov. -an edible truffle-like fungus- normally exists in a symbiotic association with Cedrus deodara (Roxb.) Loud. Because of this important association and the ecological significance as per the available literature attached to this fungus, the present study was undertaken with a specific objective to test the mycorrhizal viability of this mycobiont with this important tree species of Himalaya -the theme t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…Thereafter several studies have observed EcM association with this tree species [21,[61][62][63][64][65][66][67][68][69][70][71][72][73]. Moreover, many researchers have successfully synthesized Rhizopogon ectomycorrhizae with several conifer species under laboratory conditions [25,[74][75][76][77][78][79][80][81][82][83], beside this, the seedlings of C. deodara have been inoculated with pure cultures of several EcM fungi other than Rhizopogon sp [84][85][86][87]. However, there have been relatively very few studies confirming in vitro synthesis between R. himalayensis and C. deodara seedlings [25,83] and needs more research to characterize this association with the roots C. deodara growing in pure forests.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thereafter several studies have observed EcM association with this tree species [21,[61][62][63][64][65][66][67][68][69][70][71][72][73]. Moreover, many researchers have successfully synthesized Rhizopogon ectomycorrhizae with several conifer species under laboratory conditions [25,[74][75][76][77][78][79][80][81][82][83], beside this, the seedlings of C. deodara have been inoculated with pure cultures of several EcM fungi other than Rhizopogon sp [84][85][86][87]. However, there have been relatively very few studies confirming in vitro synthesis between R. himalayensis and C. deodara seedlings [25,83] and needs more research to characterize this association with the roots C. deodara growing in pure forests.…”
Section: Discussionmentioning
confidence: 99%
“…The microscopic characters like peridium, hymenal tissue, tramal tissues, basidia, basidioles, sterigmata, and basidiospores were recorded using Nikon eclipse E-400 microscope. The species was identified by following available literature [25,[29][30][31]46] and authenticated by DNA sequencing.…”
Section: Sample Collection Characterization and Molecular Identificat...mentioning
confidence: 99%
See 2 more Smart Citations
“…Little is known of the EMF communities of Cedrus deodara , especially out of its native range, but preliminary assessment of its EMF community in the Himalayas (Pande et al, 2004) showed association with various taxa such as: Boletus , Russula and Amanita . Other studies demonstrated a potential association with Rhizopogon (Thakur et al, 2021) and Scleroderma (Itoo and Reshi, 2014) under nursery conditions. The rooting systems of the mature Pinus halepensis and Cedrus deodara differ greatly.…”
Section: Methodsmentioning
confidence: 98%